(untitled) (Salam International Academic Journal, 2023)
The administration of justice and the safeguarding of citizens’ rights are fundamental characteristics of an Islamic government, and the judiciary plays a central and esteemed role in preserving the principles of justice within the framework of Islam. The success of any government hinges on the establishment of a robust, impartial, and independent judicial system, complete with written laws and procedural guidelines. Moreover, the application of common sense is vital to address the diverse problems that society may encounter. In contemporary times, governments view it as their responsibility to fortify, sustain, and enhance public trust through the development of an efficient judicial system It is indisputable that society expects the government to administer justice, grant rightful entitlements to individuals, curtail the influence of self-interest-driven individuals, prevent chaos, and foster a tranquil environment within society. Despite the Islamic Emirate of Afghanistan having promulgated two sets of laws, namely administrative rules of the courts and judicial rules of the courts, along with issuing various decrees to regulate matters pertaining to legal disputes, there is a lack of public awareness about these rules and regulations. This research endeavors to examine how the courts within the Islamic Emirate handle civil cases in light of the decrees of the Amir ul Mumineen and the laws promulgated by the Supreme Court of the Islamic Emirate, particularly those that are not readily accessible to the public or are not widely known. As a conclusion of this study, I have suggested some recommendations to enhance and strengthen the judicial system. The endeavor to strengthen the judicial system is a critical component of nurturing a just and orderly society, aligning with the principles of Islamic governance, and ensuring that citizens’ rights are upheld in accordance with the law.